Evaluation of Service Quality of Diving Tourism in Bali, Indonesia - Sudiarta, I Ketut (E-Journal of Tourism, 2024)
Bali diving tourism needs to be managed properly to strengthen competitiveness in the face of increasingly fierce competition. Using a set of attributes of diving tourism, this study aims to evaluate the compatibility of the diving tourism attributes that are important to divers and the performance of these attributes and to determine the actual performance of the diving tourism attributes in Bali. Data were collected through a questionnaire survey of 236 respondents regarding the importance of the 20 diving tourism attributes and their satisfaction with these attributes. As many as 13 of the 20 diving tourism attributes in Bali performed positively, meaning that the level of satisfaction exceeded the level of importance, and only one attribute performed negatively, meaning that the level of satisfaction was lower than the level of importance. Importance-Performance analysis shows that the attributes that are the competitive strengths of Bali diving tourism are coral cover, coral diversity, water visibility, dive equipment settings, divemaster competence, safety measures, and pre-dive briefing. The attributes that become weaknesses are the fish abundance, fish diversity, megafauna, and the implementation of the diving code of conduct. Diving tourism stakeholders in Bali must focus on improving the attributes that are weaknesses and maintaining the attributes that are strengths to strengthen the competitiveness of Bali diving tourism in the future.